Hybridity in the Novel “The Lowland” by Jhumpa Lahiri - Miya Gina Fatah Badjak; Bakhtiar Majid; Sulmi Magfirah (Jurnal Sinestesia, 2022)
This research discuss about the Hybridity in the novel “The Lowland” by Jhumpa Lahiri viewed from Postcolonial Theory. The research focused on the hybridity culture in the novel and the impact of hybridity culture that reflected to the character in the novel. The method of this research used descriptive analysis method to describe problems in the forms of narration and analysis. This research used postcolonial theory of Hommi Bhaba hybridity to help on understanding the hybridity, or mix of two or more culture in the primary data, then to match with the real condition in India from the library research and internet search about the important events that related to postcolonialism theory about the postcolonial era that effected into the Indian culture in the novel then caused a hybridity culture. The result of this research is, the researcher finds the forms of hybridity which is reflected through the character in the novel. The forms of hybridity in the mix of British and Indian culture are hybridity culture, hybridity language, and hybridity in race and between three forms of hybridity the researcher found the dominant one is hybridity culture. The researcher also found the impact of hybridity culture that created the blurred copy of first and second culture, and then, make the domination position of one another and inferior culture Alienation and discriminate on the “third space”.